Penguatan Public Speaking untuk Meningkatkan Profesionalisme dan Kapasitas Komunikasi Karyawan PT Spill Indonesia - Nuraryo, Imam; Basuki, Rizqy Aziz; Mardewi, Criana (Jurnal Abdimas: Sosial, Bisnis, dan Lingkungan, 2025)
Public speaking is a critical skill for employees across various professional fields, especially in work environments that demand effective and representative communication. In today’s dynamic workplace, public speaking is not only essential for conveying information but also for building trust, persuading audiences, and reinforcing corporate image. However, many employees still lack access to formal opportunities for developing this skill. This community engagement program aimed to enhance the public speaking competence of employees at PT SPILL Indonesia through an interactive and practical training module. The training methods included interactive lectures, role-play simulations, group discussions, and direct speaking practice. Participants were guided to understand verbal and non-verbal communication techniques, manage anxiety, and develop structured and engaging presentations. The results indicated a significant improvement in participants’ understanding of public speaking principles, narrative construction, and confidence in public speaking. High levels of enthusiasm throughout the training reflected a strong demand for communication skill development in the workplace. This program demonstrates that a participatory and contextual training approach can serve as an effective strategy to enhance professional communication capacity within corporate environments.